Comparative analysis of decentralized heating systems of residential buildings with the use of electricity - Мазуренко, Антон Станиславович; Климчук, Олександр Андрійович; Шраменко, Олександр Миколайович; Сичова, Олена Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2014)
On the threshold of the heating season, Ukraine is in a difficult energy situation. There is a serious shortage of fossil fuels both gaseous and solid. Electricity can become the most viable alternative to fossil fuels in Ukraine. Ukraine produces enough electricity to meet its own needs. However, outdated electricity supply system networks will not allow to resolve the heating problem next winter by a simple transition from gas to electricity. It is necessary to develop a set of measures that allows to resolve the issue of heat supply systems transition to electricity without significant reconstruction of external networks. Feasibility study of transition ways of heating systems to the electricity use was carried out in the paper. The study has shown that only a comprehensive approach allows to solve the problem of transition of heating systems to electricity without reconstruction of external electricity supply systems. A comprehensive approach should include a number of measures, aimed at reducing the total energy consumption of the building. At the first stage, thermomodernization of buildings should be held, namely wall insulation, replacement of glass with energy-saving. At the second stage, hydraulic balancing of the heating system is organized. The third stage involves replacing the heat source with a heat pump and direct cylinder and can be considered final. Such measures allow to reduce energy consumption for heating needs by at least two times.